The Local Linear M-Estimation with Missing Response Data - Shuanghua Luo; Cheng-Yi Zhang; Fengmin Xu (Journal of Applied Mathematics)
This paper studies the nonparametric regressive function with missing response data. Three local linear M-estimators with the robustness of local linear regression smoothers are presented such that they have the same asymptotic normality and consistency. Then finite-sample performance is examined via simulation studies. Simulations demonstrate that the complete-case data M-estimator is not superior to the other two local linear M-estimators.